Polo-Like Kinase 4’s Critical Role in Cancer Development and Strategies for Plk4-Targeted Therapy - Zhang, Xiaoyang; Wei, Cheng; Liang, Hao; Han, Lei (Frontiers in Oncology, 2021)
Polo-like kinases (Plks) are critical regulatory molecules during the cell cycle process. This family has five members: Plk1, 2, 3, 4, and 5. Plk4 has been identified as a master regulator of centriole replication, and its aberrant expression is closely associated with cancer development. In this review, we depict the DNA, mRNA, and protein structure of Plk4, and the regulation of Plk4 at a molecular level. Then we list the downstream targets of Plk4 and the hallmarks of cancer associated with these targets. The role of Plk4 in different cancers is also summarized. Finally, we review the inhibitors that target Plk4 in the hope of discovering effective anticancer drugs. From authors’ perspective, Plk4 might represent a valuable tumor biomarker and critical target for cancer diagnosis and therapy.